2022
DOI: 10.1002/bdr2.1988
|View full text |Cite
|
Sign up to set email alerts
|

The study of expression levels of DNA methylation regulators in patients affected with congenital heart defects (CHDs)

Abstract: Background: Congenial heart defects (CHDs) have multifactorial etiology with complex interplay of genetic and environmental factors. Environmental impact can have epigenetic mechanism of CHD development. Many studies have reported the causal association between CHD and distinct DNA methylation profile which is one of the key epigenetic events, which has vital role in normal embryonic development. The products of DNMT1, DNMT3A, DNMT3B, and MBD2 are important regulators of DNA methylation process.Changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…Joshi et al found that the expression levels of DNMT3A and DNMT3B were significantly reduced in the blood of patients under the age of 21 with several forms of congenital heart disease, such as ventricular or atrial septal defects and pulmonary stenosis, suggesting that decreased DNMT3 activity and the related genome's hypomethylation may contribute to the pathogenesis of CHDs [144]. Sheng et al found that patients with tetralogy of Fallot (TOF) have significantly lower methylation levels of LINE-1 and lower global DNA methylation levels compared to healthy individuals [145].…”
Section: Dnmts In Congenital Heart Defects and Paediatric Cvdmentioning
confidence: 99%
“…Joshi et al found that the expression levels of DNMT3A and DNMT3B were significantly reduced in the blood of patients under the age of 21 with several forms of congenital heart disease, such as ventricular or atrial septal defects and pulmonary stenosis, suggesting that decreased DNMT3 activity and the related genome's hypomethylation may contribute to the pathogenesis of CHDs [144]. Sheng et al found that patients with tetralogy of Fallot (TOF) have significantly lower methylation levels of LINE-1 and lower global DNA methylation levels compared to healthy individuals [145].…”
Section: Dnmts In Congenital Heart Defects and Paediatric Cvdmentioning
confidence: 99%